Amphetamine-Related Ischemic Colitis Causing Gastrointestinal Bleeding. Issue 3 (1st July 2016) - Panikkath, Ragesh; Panikkath, Deepa
Abstract : A 43-year-old woman presented with acute lower intestinal bleeding requiring blood transfusion. Multiple initial investigations did not reveal the cause of the bleeding. Colonoscopy performed 2 days later showed features suggestive of ischemic colitis. On detailed history, the patient admitted to using amphetamines, and her urine drug screen was positive for them. She was managed conservatively and advised not to use amphetamines again. She did not have any recurrence on 2-year follow-up.